Benefits, barriers and recommendations for youth engagement in health research: combining evidence-based and youth perspectives - Bailey, Katherine; Allemang, Brooke; Vandermorris, Ashley; Munce, Sarah; Cleverley, Kristin; Chisholm, Cassandra; Cohen, Eva; Davidson, Cedar; El Galad, Asil; Leibovich, Dahlia; Lowthian, Trinity; Pillainayagam, Jeanna; et al. (Université d'Ottawa | University of Ottawa, 2024)
Abstract Background Youth engagement refers to the collaboration between researchers and youth to produce research. Youth engagement in health research has been shown to inform effective interventions aimed at improving health outcomes. However, limited evidence has identified promising practices to meaningfully engage youth. This synthesis aims to describe youth engagement approaches, frameworks, and barriers, as well as provide both evidence-based and youth-generated recommendations for meaningful engagement. Main body This review occurred in two stages: 1) a narrative review of existing literature on youth engagement and 2) a Youth Advisory Council (YAC) to review and supplement findings with their perspectives, experiences, and recommendations. The terms ‘youth engagement’ and ‘health research’ were searched in Google Scholar, PubMed, Web of Science, Scopus, and PsycINFO. Articles and non-peer reviewed research works related to youth engagement in health research were included, reviewed, and summarized. The YAC met with research team members and in separate youth-only forums to complement the narrative review with their perspectives. Types of youth engagement include participation as research participants, advisors, partners, and co-investigators. Barriers to youth engagement were organized into youth- (e.g., time commitments), researcher- (e.g., attitudes towards youth engagement), organizational- (e.g., inadequate infrastructure to support youth engagement), and system-level (e.g., systemic discrimination and exclusion from research). To enhance youth engagement, recommendations focus on preparing and supporting youth by offering flexible communication approaches, mentorship opportunities, diverse and inclusive recruitment, and ensuring youth understand the commitment and benefits involved. Conclusions To harness the potential of youth engagement, researchers need to establish an inclusive and enabling environment that fosters collaboration, trust, and valuable contributions from youth. Future research endeavors should prioritize investigating the dynamics of power-sharing between researchers and youth, assessing the impact of youth engagement on young participants, and youth-specific evaluation frameworks.

Plain English summary Engaging and partnering with youth in research related to healthcare is important, but often not done well. As researchers, we recognize that youth perspectives are needed to make sure we are asking the right questions, using appropriate research methods, and interpreting the results correctly. We searched the literature to identify challenges researchers have faced engaging youth in health research, as well as strategies to partner with youth in a meaningful way. We worked closely with 11 youth from across Canada with experience in healthcare, who formed a Youth Advisory Council. The youth advisors reviewed the literature we found and discussed how it fit with their own experiences and perspectives through group meetings with the research team. Youth advisors divided into four groups to co-author parts of this paper, including identifying the importance, benefits, and challenges of engaging in research and providing reflections on their positive and negative previous experiences as youth advisors. This paper provides an overview of recommendations for researchers to engage with youth in a meaningful way, including how they communicate and meet with youth, recognize their contributions, and implement feedback to improve the experiences of youth partners.